Lazer na perspectiva do envelhecimento - Silva, Sônia Pereira da (Universidade Federal do Tocantins, 2024)
This Course Completion Work proposes to analyze the theme of leisure from the perspective of aging, bringing reflections on age categories, their social construction, the process of population aging, identified as a global trend due to the constant increase in recent decades, nationally and internationally, of the portion of the population aged sixty years or over and the right to leisure for a better quality of life for elderly people. We sought to understand, beyond biology and nature, social, cultural and demographic aspects related to this topic and this social process based on studies in the human and social sciences. The methodology adopted, of a qualitative nature, involved bibliographical research on the topic addressed. In the end, it is considered that leisure policy and old age require that they be understood as rights, whose experiences are not universal and homogeneous according to various social belongings (class, gender, ethnicity).